The nature of managerial moral standards - Bird, Frederick (Journal of business ethics, 1987)
Descriptions of how managers think about the moral questions that come up in their work lives are analyzed to draw out the moral assumptions to which they commonly refer. The moral standards thus derived are identified as (1) honesty in communication, (2) fair treatment, (3) special consideration, (4) fair competition, (5) organizational responsibility, (6) corporate social responsibility, and, (7) respect for law. It is observed that these normative standards assume the cultural form of social conventions but because managers invoke them as largely private intuitions, their cultural status remains precarious and unclear. This is the second in a research series of three papers.